ANALISIS PERENCANAAN DAN PENGENDALIAN DALAM PENCAIRAN DANA PADA PENGADAAN ALAT-ALAT KEDOKTERAN PADA DINAS KESEHATAN KOTA LHOKSEUMAWE - Maulina, Isra (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2021)
Good management will provide a reference or description of how the health office is managed in a transparent manner, there is independence, accountability, and there is responsibility and fairness so that financial performance at the lhokseumawe city health office can be achieved in accordance with the vision and mission of the health office. This study aims to determine how the process of implementing planning and control in the disbursement of funds for the procurement of medical equipment at the health office of lhokseumawe city. This research uses a qualitative approach with descriptive and analysis. Data collection in this study was carried out through interviews and documentation. Interviews were conducted with related parties and knew about the disbursement of funds for the procurement of goods / services at the lhokseumawe city health office in 2011. The results obtained indicate that the control planning process in disbursing funds for the procurement of medical devices in the lhokseumawe city health office in 2001 has not fully used the applicable rules so that the implementation of goods/ services is not in accordance with the reality and expectations of the community in general. This is evidenced by the delay in the distribution of medical devices at the puskesmas and the absence of an official report on the receipt of goods while the disbursement of funds was carried out 100%. This condition gave birth to a financial management system that was not transparent and accountable.